2012
DOI: 10.1371/journal.pntd.0001972
|View full text |Cite
|
Sign up to set email alerts
|

Severe Anemia in Papua New Guinean Children from a Malaria-Endemic Area: A Case-Control Etiologic Study

Abstract: BackgroundThere are few detailed etiologic studies of severe anemia in children from malaria-endemic areas and none in those countries with holoendemic transmission of multiple Plasmodium species.Methodology/Principal FindingsWe examined associates of severe anemia in 143 well-characterized Papua New Guinean (PNG) children aged 0.5–10 years with hemoglobin concentration <50 g/L (median [inter-quartile range] 39 [33]–[44] g/L) and 120 matched healthy children (113 [107–119] g/L) in a case-control cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 49 publications
4
42
0
1
Order By: Relevance
“…Our results correlate with the data of other researchers who studied the PVI-associated malaria in children in malaria-endemic regions: among children under 5 years, the absolute majority of cases of PVI was accompanied by a complicated course of malaria [4,10,14].…”
Section: Discussionsupporting
confidence: 90%
“…Our results correlate with the data of other researchers who studied the PVI-associated malaria in children in malaria-endemic regions: among children under 5 years, the absolute majority of cases of PVI was accompanied by a complicated course of malaria [4,10,14].…”
Section: Discussionsupporting
confidence: 90%
“…Anemia in malaria is multifactorial and mainly due to haemolysis and dyserythropoiesis [39]. Recently, two studies in children of Papua New Guinea showed that certain common infections, and especially B19V-infection can play a critical role in the etiology of severe anemia besides other factors, such as malnutrition and iron deficiency, in a highly endemic area for malaria [21,40]. This finding was further supported by yet another study showing that high B19V IgM levels were significantly associated with severe anemia in Kenyan children [20].…”
Section: Discussionmentioning
confidence: 99%
“…B19V infection and malaria. Of relevance to potential vaccine development, B19V occurs in areas where malaria is endemic (747), and serological surveys have suggested worse chronic anemia in children who are seropositive for B19V (IgG) or have evidence of recent infection (IgM and viral DNA) (748)(749)(750)(751). Acute B19V infection may occur concurrently with malaria (752,753).…”
Section: Clinical Manifestations Diseases Caused By B19v Infectionmentioning
confidence: 99%